2010
DOI: 10.1083/jcb.201002133
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Mps1 activity is required in mitosis to recruit O-Mad2 to the Mad1–C-Mad2 core complex

Abstract: To satisfy the mitotic checkpoint and drive chromosome congression, the Mps1 kinase lets go of kinetochores by phosphorylating itself in trans (see also related papers by Maciejowski et al. and Santaguida et al. in this issue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
430
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(482 citation statements)
references
References 34 publications
46
430
5
1
Order By: Relevance
“…Even in the absence of SAC activators, both classes of MPS1 inhibitors markedly increased the rate of chromosome misalignments resulting from erroneous MT-KT attachments and promoted a premature anaphase entry (i.e., before the formation of a correct equatorial metaphase plate). These results are in line with previous findings obtained with other MPS1-specific inhibitors, [8][9][10]12,15,47 upon MPS1 depletion 16,24 or following the conditional knockout of TTK, 11 confirming the central implication of this mitotic kinase in SAC function and chromosome congression. Upon exposure to MPS1 inhibitors, colorectal carcinoma cells displayed severely abnormal anaphases, and, as they progressed in mitosis, they underwent two alternative catastrophic fates: (i) they divided in a bipolar (often asymmetrical) manner, generating two aneuploid cells that most often died in the following interphase, or (ii) they failed to complete cytokinesis and hence became hyperploid.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Even in the absence of SAC activators, both classes of MPS1 inhibitors markedly increased the rate of chromosome misalignments resulting from erroneous MT-KT attachments and promoted a premature anaphase entry (i.e., before the formation of a correct equatorial metaphase plate). These results are in line with previous findings obtained with other MPS1-specific inhibitors, [8][9][10]12,15,47 upon MPS1 depletion 16,24 or following the conditional knockout of TTK, 11 confirming the central implication of this mitotic kinase in SAC function and chromosome congression. Upon exposure to MPS1 inhibitors, colorectal carcinoma cells displayed severely abnormal anaphases, and, as they progressed in mitosis, they underwent two alternative catastrophic fates: (i) they divided in a bipolar (often asymmetrical) manner, generating two aneuploid cells that most often died in the following interphase, or (ii) they failed to complete cytokinesis and hence became hyperploid.…”
Section: Discussionsupporting
confidence: 82%
“…10,15,47 Conversely, it has been reported that the absence of MPS1 favors cytokinesis failure and polyploidy. 8,16,48 This discrepancy may reflect differences in the experimental models or the strategy used for MPS1 inhibition. 7,11 Indeed, as the inactivation of 490% of MPS1 is required for the induction of mitotic abnormalities, 7,11 in some studies MPS1 inhibition may have been partial, yielding suboptimal effects on mitosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In budding yeast mitosis, Mps1 regulates mitotic chromosome alignment by promoting kinetochore biorientation independently of Ipl1 (aurora B in humans) (31), but in budding yeast meiosis Mps1 must collaborate with Ipl1 to mediate meiotic kinetochore biorientation (32). In humans, Mps1 regulates chromosomal alignment by modulating aurora B kinase activity (33), but recent chemical biology studies show that Mps1 kinase activity is important for proper chromosome alignment and segregation, independently of aurora B (22,(34)(35)(36). Therefore whether Mps1 regulates chromosome alignment through modulation of aurora B kinase activity is still under debate (37).…”
mentioning
confidence: 99%
“…It is thought that the closed conformation can catalyse the binding of the open form to Cdc20, and once bound the open form is converted to the closed form. Thus, a population of closed Mad2 stably bound to unattached kinetochores through the Mad1 protein continually promotes the binding of open Mad2 to Cdc20 by a mechanism that requires the Mps1 kinase [82]. The Mad2 -Cdc20 complex subsequently binds to the Mad3/BubR1-Bub3 complex [83,84], which prevents Cdc20 forming the substrate receptor on the APC/C.…”
Section: Local and Global Decisions At Kinetochores: The Spindle Assementioning
confidence: 99%